Relação entre toxicidade urêmica, anemia e perda auditiva neurossensorial em indivíduos com doença renal crônica: um estudo prospectivo - Lopez, Priscila Suman [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Patients in the chronic kidney disease (CKD) have a higher risk of developing sensorineural hearing loss (SNHL) concerning the general population, independently of age, gender, diabetes and/ or hypertension. Aim: To study the relationship between uremic toxicity, anemia, stage of CKD and SNHL in CKD patients followed for two years. Methods: Prospective clinical study in a tertiary hospital. The blood measures and hearing loss were performed by the audiometry (PTA), evoked otoacoustic emissions (OAE) and auditory brainstem response (ABR) tests in two moments (M1 was the baseline and M2 two years later). Forty-three(43) patients were included and they were selected by using these criteria: they suffered from CKD at any stage, they underwent any type of treatment in the local institution, maximum age of 60, tympanometric curve A in both ears and moments, without congenital hearing loss, genetic syndromes, mental disabilities, excessive noise exposure, no administration aminoglycosides and/or renal transplantation. Results: The most patients were male (58%), of white race (91%), median age 53 years, 40 months of CKD and arterial hypertension (65% in M1 and 67% in M2). In M1, the conservative method was more frequent (63%) with stage 4 and 5 CKD (37 %). In the second evaluation 25% of the patients showed worsening of CKD stage. SNHL affected 28% of patients in M1 and 33% in M2, absence of EOE- T was observed in 34 % of patients in M1 and 45% in M2. ABR changes were observed in 21% of patients in M1 and 26 % in M2. Hearing deterioration was observed in 24% of PTA patients, 11% of EOE-T and 16% of ABR. Among the blood markers, high initial levels of beta2- microglobulin and low initial levels hematocrit and hemoglobin were associated with higher risk of abnormal ABR. The stage of CKD was not associated with sensorineural hearing loss

Introdução: Portadores da doença renal crônica (DRC) têm maior risco de desenvolver perda auditiva neurossensorial (PANS) em relação à população geral, independentemente de idade, sexo, diabetes e hipertensão arterial. Objetivos: Estudar relações entre toxicidade urêmica, anemia, progressão do estádio da DRC e PANS em pacientes com DRC, durante dois momentos: inicial (M1) e após dois anos (M2). Casuística e métodos: Estudo clínico prospectivo, em hospital terciário, com avaliação sanguínea e auditiva em dois momentos (M1 inicial e M2 dois anos depois), esta composta por Audiometria Tonal Limiar (ATL), Emissões Otoacústicas Evocadas Transientes (EOE-t) e Potencial Evocado Auditivo de Tronco Encefálico (PEATE). Foram incluídos 43 pacientes que atenderam aos seguintes critérios de inclusão: ser portador de DRC em quaisquer estádio ou método de tratamento, sendo este realizado na instituição local, ter até 60 anos, comparecer às duas avaliações, apresentar curva timpanométrica “A” nas duas orelhas em ambas as avaliações, não ter deficiência auditiva congênita, síndromes genéticas, deficiência mental, exposição excessiva ao ruído, não ter sido submetido a transplante renal nem ter ingerido antibióticos aminoglicosídeos. Resultados: Predomínio do sexo masculino (58%), raça branca (91%), idade mediana de 53 anos e de DRC de 40 meses. Pacientes hipertensos representaram 65% da amostra em M1 e 67%, em M2, sendo, em M1, o método conservador mais frequente (63%), com estádios da DRC 4 e 5 (37%). Após dois anos, 25% dos pacientes apresentaram progressão do estádio da DRC; a PANS, na ATL, afetou 28% dos pacientes em M1 e 33%, em M2; ausência de EOE-t foi observada em 34% dos pacientes em M1 e, em M2, 45%. PEATE alterado foi observado em 21% dos pacientes em M1 e em 26%, em M2. Ao final do estudo, mudança na classificação da ATL foi observada em 24% dos pacientes ...
Keywords: Rins - Doenças; Insuficiencia renal cronica; Anemia; Uremia; Disturbios da audição; Renal insufficiency, Chronic